Neutral Technological Change and the Skill Premium - Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2000)
We construct a two sector general equilibrium model in which one sector produces a homogeneous good and the other sector produces a vertically differentiated good. We demonstrate that uniform (across sectors) and (Hicks) neutral technological change can cause an increase in the skill premium.
Keywords: 330; Technological change; skill premium; differentiated products